Memory in Action: Clothing, Art, and Authenticity in Anthropological Dioramas (New York, 1900) - Etienne, Noémie (Material Culture Review)

(untitled) (Cape Breton University Press, 2014)
Abstract Anthropological dioramas are museographic installations created in order to display artifacts. They are comprised of exotic material culture products as well as plaster sculptures, generated to show and contextualize the objects. In this article, the case of clothing made for the New York State Museum’s manikins is studied. I demonstrate how their authenticity is manufactured through certain practices, including embroidery, tanning, and dyeing. Paradoxically enough, replication techniques guarantee the object’s authenticity. Here, the proper origin of the thing matters less than the identity of those who manipulated the artifacts.